The unbound : an Archived novel - Schwab, Victoria (Schwab, Victoria. Archived novel., 2015)
Starting her junior year at Hyde School, Mackenzie Bishop, a Keeper tasked with stopping violent Histories from escaping the Archive, becomes the prime suspect when several people vanish without a trace.